Deep-sea biotope classification using opportunistic sampling: insights for future management - Heidy Q. Dias; Kerstin Kröger; Andrew J. Wheeler; Riccardo Arosio; Audrey Recouvreur; Tim P. Le Bas; Isobel A. Yeo; Patrick C. Collins (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Assessment of PRISMA Level-2 Hyperspectral Imagery for Large Scale Satellite-Derived Bathymetry Retrieval - Evangelos Alevizos; Tim Le Bas; Dimitrios D. Alexakis (Marine Geodesy, 2022)

Monitoring mosaic biotopes in a marine conservation zone by autonomous underwater vehicle - Noëlie M.A. Benoist; Kirsty J. Morris; Brian J. Bett; Jennifer M. Durden; Veerle A.I. Huvenne; Tim P. Le Bas; Russell B. Wynn; Suzanne J. Ware; Henry A. Ruhl (Conservation Biology, 2019)
The number of marine protected areas (MPAs) has increased dramatically in the last decade and poses a major logistic challenge for conservation practitioners in terms of spatial extent and the multiplicity of habitats and biotopes that now require assessment. Photographic assessment by autonomous underwater vehicle (AUV) enables the consistent description of multiple habitats, in our case including mosaics of rock and sediment. As a case study, we used this method to survey the Greater Haig Fras marine conservation zone (Celtic Sea, northeast Atlantic). We distinguished 7 biotopes, detected statistically significant variations in standing stocks, species density, species diversity, and faunal composition, and identified significant indicator species for each habitat. Our results demonstrate that AUV‐based photography can produce robust data for ecological research and practical marine conservation. Standardizing to a minimum number of individuals per sampling unit, rather than to a fixed seafloor area, may be a valuable means of defining an ecologically appropriate sampling unit. Although composite sampling represents a change in standard practice, other users should consider the potential benefits of this approach in conservation studies. It is broadly applicable in the marine environment and has been successfully implemented in deep‐sea conservation and environmental impact studies. Without a cost‐effective method, applicable across habitats, it will be difficult to further a coherent classification of biotopes or to routinely assess their conservation status in the rapidly expanding global extent of MPAs.

Seabed mapping in the Pelagie Islands marine protected area (Sicily Channel, southern Mediterranean) using Remote Sensing Object Based Image Analysis (RSOBIA) - Sara Innangi; Renato Tonielli; Claudia Romagnoli; Francesca Budillon; Gabriella Di Martino; Michele Innangi; Roberta Laterza; Tim Le Bas; Claudio Lo Iacono (Marine Geophysical Research, 2019)

Multibeam sonar backscatter data processing - Alexandre C. G. Schimel; Jonathan Beaudoin; Iain M. Parnum; Tim Le Bas; Val Schmidt; Gordon Keith; Daniel Ierodiaconou (Marine Geophysical Research, 2018)

Control of the repeatability of high frequency multibeam echosounder backscatter by using natural reference areas - Marc Roche; Koen Degrendele; Christophe Vrignaud; Sophie Loyer; Tim Le Bas; Jean-Marie Augustin; Xavier Lurton (Marine Geophysical Research, 2018)

Peter C. Wille, Sound images of the ocean in research and monitoring - Tim Le Bas (Marine Geophysical Research, 2008)